Altitude strategies for maximizing cycle speed - Swanson, G. (13. International Hypoxia-Symposium, February, 19-22, 2003, Banff, Alberta (Kanada), 2003)
Endurance cycling speed can be enhanced by road racing at higher altitudes. However, a trade-off exists between the reduced drag of altitude and the reduced aerobic power associated with the lower oxygen availability of altitude. These concepts suggest there may be an optimal altitude for maximizing cycling speed. This altitude would balance diminished oxygen availability with diminished drag characteristics to produce a maximum speed. Capelli & di Prampero (Eur. J. Appl. Physiol. 71:469-471, 1995) have determined from basic principles that the optimal one hour endurance altitude is about 16,000 feet for a rode bike. Our approach extends their work by utilizing known physics of air density, a mathematical model of cycling and literature data about the altitude effect on reduced aerobic apacity. This approach results in a mathematical model from which the optimal altitude is determined. For a rode bike, neglecting rolling resistance, our results suggest an optimal altitude of 15,400 feet (similar to Capelli and di Prampero). However, for a recumbent bike, a faring can be used to further educe drag so that rolling resistance becomes a factor and cannot be neglected. Under these conditions, the model predicts an optimal endurance altitude of about 5,700 feet. Furthermore, when a 30 s anaerobic trust to exhaustion is added to a base line endurance speed so as to maximize the peak velocity, the optimal altitude shifts to about 10,000 feet. Model sensitivity nalysis indicates that these altitude estimates have a rather broad confidence interval. Therefore, our results suggest that "mile-high" altitudes maximize endurance speed but "two-mile high" altitudes maximize peak speed. Interesting, the Colorado Speed Challenge held in Alamosa (1993) at an altitude of about 8000 feet may have been held at an altitude close to optimal and resulted in average 200 meter speeds of near 70 mph.